Drugs for metabolic conditions and prostate cancer death in men on GnRH agonists. (17th October 2017) - Bosco, Cecilia; Wong, Chloe; Garmo, Hans; Crawley, Danielle; Holmberg, Lars; Hammar, Niklas; Adolfsson, Jan; Stattin, Pär; Van Hemelrijck, Mieke
Abstract : Objective: To evaluate whether drugs for metabolic conditions influence prostate cancer‐specific mortality in men starting gonadotrophin‐releasing hormone (GnRH) agonists, as it is unclear whether metabolic syndrome and its related drugs is affecting treatment response in men with prostate cancer on GnRH agonists. Patients and Methods: We selected all men receiving GnRH agonists as primary treatment in the Prostate Cancer data Base Sweden (PCBaSe) ( n = 9267). Use of drugs for metabolic conditions (i.e. anti‐diabetes, anti‐dyslipidaemia, and antihypertension) in relation to all‐cause, cardiovascular disease (CVD), and prostate cancer‐specific death were studied using multivariate Cox proportional hazard and Fine and Gray competing regression models. Results: In all, 6322 (68%) men used at least one drug for a metabolic condition at GnRH agonist initiation: 46% on antihypertensive drugs only, 32% on drugs for dyslipidaemia and hypertension, and ~10% on drugs for more than two metabolic conditions. Cox models indicated a weak increased risk of prostate cancer death in men who were on drugs for hypertension only (hazard ratio [HR] 1.12, 95% confidence interval [CI] 1.03–1.23) or drugs for hyperglycaemia (HR 1.19, 95% CI 1.06–1.35) at GnRH agonist initiation. However, upon taking into account competing risk from CVD death, none of the drugs for metabolic conditions were associated with an increased risk of prostate cancer death. Conclusion: We did not find evidence for a better or worse response to GnRH agonists in men with prostate cancer who were also on drugs for hypertension, dyslipidaemia, or hyperglycaemia.